Resistensi dalam Wacana Dhagelan Youtube Cak Silo Cs - Puspita Indriani; Darni Darni; Udjang Pairin; Budinuryanta Yohanes (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This research aims to reveal resistance strategies to form humor in Cak Silo Cs' Dhagelan YouTube content. The research data source is the YouTube content of Cak Silo Cs episode Cak Silo Jualan Pentol which was uploaded on March 22 2020. The object of research is lingual units which indicate resistance. Next, listening and interpreting were carried out and explained descriptively qualitatively and analyzed using the functional pragmatic method. The research results show that the resistance used only includes three forms of the four existing forms. 1) reactance by mocking with reasons that are not commonly used, and saying clearly "no" or "don't" accompanied by reasons that are not commonly used. 2) distrust expressed by "don't want" accompanied by reasons that are not commonplace/ 3) supervision expressed by giving suggestions, asking and agreeing accompanied by an explanation of the refusal.